Children's Literature in Algeria: Reality and Themes - rebha Khaldi (Journal of Science and Knowledge Horizons, 2025)
Children's literature is considered a literature characterized by a specificity that distinguishes it from adult literature. It requires a sufficient and important amount of care given its great importance in forming the child's personality and directing him properly. It relies primarily on high ideals and derives its intellectual components from the teachings of Islam, to achieve various goals, including psychological, social, and mental